2016
DOI: 10.4269/ajtmh.16-0398
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Linkage to Care for Hepatitis B Virus Infection: A Qualitative Analysis in Burkina Faso, West Africa

Abstract: Hepatitis B virus (HBV) infection is a critical global health problem. The World Health Organization (WHO) has recently developed a global elimination strategy for HBV infection. Increasing access to screening, liver assessment, and antiviral treatment are crucial steps in achieving this goal. Little is known, however, about obstacles to linkage to care in low- and middle-income countries. Using a grounded theory approach, this qualitative study sought to characterize the diagnostic itineraries of people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 24 publications
6
46
0
Order By: Relevance
“…The study revealed that relatives’ treatment experience can help patients become aware of their own diseases. This result was similar to that of previous studies, indicating that patients received conventional treatment on the basis of family members’ personal healthcare experiences (Fang & Stewart, ; Giles‐Vernick et al, ). Some studies have indicated that patients refused screenings and follow‐up because of the fear of unfavourable results and social stigma (Ezbarami et al, ; Yang, ), but the current study did not produce similar results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The study revealed that relatives’ treatment experience can help patients become aware of their own diseases. This result was similar to that of previous studies, indicating that patients received conventional treatment on the basis of family members’ personal healthcare experiences (Fang & Stewart, ; Giles‐Vernick et al, ). Some studies have indicated that patients refused screenings and follow‐up because of the fear of unfavourable results and social stigma (Ezbarami et al, ; Yang, ), but the current study did not produce similar results.…”
Section: Discussionsupporting
confidence: 91%
“…The study revealed that relatives' treatment experience can help patients become aware of their own diseases. This result was similar to that of previous studies, indicating that patients received conventional treatment on the basis of family members' personal healthcare experiences (Fang & Stewart, 2018;Giles-Vernick et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the southeast region of Asia, about 100 million people have chronic HBV infection. The prevalence of chronic viral hepatitis in this region is 30-times more than that of human immunodeficiency virus (HIV) [25].…”
Section: Introductionmentioning
confidence: 98%